Pengembangan Media Augmented Reality Berbasis Asemblar Edu pada Mata Pelajaran IPA untuk Siswa Madrasah Ibtidaiyah - Hana Lestari; Rahmawati, Ima; Alma Amalia Fauziah (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to develop augmented reality-based learning media using Asemblar Edu for science subjects in Madrasah Ibtidaiyah Sahid, focusing on understanding the concept of the digestive system. The research employs the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. In the analysis phase, student needs and issues in learning were identified through interviews and surveys conducted at MI Sahid, involving 25 fifth-grade students and 2 teachers, revealing the necessity for a more interactive learning approach. The learning media was designed with storyboards and engaging content, then developed and tested in the classroom. Pretest results showed an average score of 49%, which increased to 84.67% in the posttest, indicating a significant improvement in understanding. Student responses to the media averaged 89.55%, categorized as very good. Feedback from both students and teachers indicated that the media effectively enhanced engagement and motivation in learning. This study concludes that the use of augmented reality media is effective in improving students' understanding of science concepts at MI Sahid. It is hoped that the findings can serve as a reference for educators in integrating technology into learning and encourage the development of similar media for other subjects in elementary education.